Pemanfaatan Transformasi Digital Mindset dalam Kewirausahaan UMKM untuk Pengembangan Ekonomi Lokal - Riski Annisa; Raja Sabaruddin; Panny Agustia Rahayuningsih; Monikka Nur Winnarto (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2023)
This study aims to explore the utilization of digital mindset transformation in SME entrepreneurship through community engagement activities. In the rapidly evolving digital era, SMEs face complex challenges in adopting digital technologies and transforming their business behaviors. This community engagement involves training, guidance, and collaboration with SMEs to strengthen their understanding of the importance of digital mindset transformation. The main findings of this community engagement initiative demonstrate that digital mindset transformation can have positive impacts on SME entrepreneurship. SMEs that embrace digital mindset transformation tend to achieve better business growth, enhance operational efficiency, adapt to market changes, and make better strategic decisions. Furthermore, community engagement activities significantly contribute to the development of SME entrepreneurship, community development, and local economic empowerment. The potential implications of this initiative include improved quality and competitiveness of SMEs in the digital era. Therefore, recommendations for further development involve expanding collaborations among universities, governments, and relevant stakeholders, intensifying efforts in digital infrastructure development, and exploring other aspects of digital transformation such as cyber security and e-commerce.